Penolakan Pemerintah Papua New Guinea (PNG) Terhadap Keterlibatan Tentara Nasional Indonesia (TNI) Dalam Operasi Pembebasan Sandera WNI di Papua New Guinea Tahun 2015 - Fani Aprilia Perdani (HI 16 UMY 013, 2016)
*13 Papua New Guinea (PNG) is a nation state member of nation commonwealth from England and got their independence on 1975. Geographically, Papua New Guinea is located in the east of Indonesia. That makes Papua New Guinea has land border with Indonesia in the west. Papua New Guinea and Indonesia are bordered by Wutun Village, Province of Sandaun, Papua New Guinea and Skouw Village, Muara Tami District, Jayapura, Indonesia. It makes border conflict often accour between both countries. In the finally, in 1979 Papua New Guinea and Indonesia make border cooperation. In September 9th 2015, there are two hostage from Indonesia that hostaged by armed civilians Papua New Guineans because they cut some trees at border. After that, Indonesia government asked for permission to do liberation operation by TNI (military of Indonesia). Unfortunatelly, the permission wa refused by Papua New Guinea, Prime Minister Peter O’neil. This aims of this research is intended to analyze the reasons Papua New Guinea refused to give permission for the military. The method of research put the decision of Papua New Guinea as the unit of analysis and geographic, social, and political Papua New Guinea government as a unit of explanation. This research is based on the information that is collected from data of political system of Papua New Guinea (Prime Minister Peter O'neil), geographical and social conditions around hostage area in Papua New Guinea. The decision that made by Prime Minister Peter O'neil will be analyzed through theory of decision making by Graham T. Allison. The decision making process is made base on the level of rationality. In the finally, the decision of Papua New Guinea refused the participation of Indonesian military in liberation operation is indicated as the rational decision. It can be said rational because not only there are four basic concepts of rational actor, namely: Goal and objectives, Alternatives, Consequences, and Choice. But also, there are three supporting elements of a decision can be called rational namely: intellectual considerations, long-term goal, and monolithic government conditions. The main results show that the decision of Papua New Guinea provides a rational profit to its government.